Development Mode of Regional Electricity Market in South China. (October 2019) - Sun, Qian; Li, Xiaolei; Tian, Lin; Fan, Pengfei; Yang, Junwei; Lu, En; Huang, Zhisheng; Qin, Jie
Abstract: In recent years, China's electricity market reform has continued to deepen, and the construction of the electricity market has been accelerating. According to the national power pilot reform policy, the southern regional electricity market will start with the Guangdong spot market, and then gradually develop to the southern spot market. In this paper, the realization method of power market integration is analysed, and several paths for provincial market to develop into regional spot market are put forward according to the characteristics of Southern regional power system.